2012
DOI: 10.1659/mrd-journal-d-12-00054.1
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Dependence of Springs in the Midwestern Himalayan Hills of Uttarakhand

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The few studies published on this matter are based on small, scattered areas (Negi and Joshi 2004;Vashisht and Sharma 2007;Tambe et al 2012;Tarafdar 2013;Sharma et al 2016;Kumar and Sen 2017a, b;Paramanik 2017) and reported results show significant variations across the HKH. While spring-discharge variation appears to be consistent with rainfall in Sikkim in the east (Tambe et al 2012) and Uttarakhand in the central-western Himalaya (Agarwal et al 2012), it shows an inverse pattern with monthly rainfall in the western Himalayan springs of Kashmir (Negi et al 2012). These trends suggest that, in addition to precipitation, other causal factors and localized impacts should also be investigated.…”
Section: Springsmentioning
confidence: 90%
“…The few studies published on this matter are based on small, scattered areas (Negi and Joshi 2004;Vashisht and Sharma 2007;Tambe et al 2012;Tarafdar 2013;Sharma et al 2016;Kumar and Sen 2017a, b;Paramanik 2017) and reported results show significant variations across the HKH. While spring-discharge variation appears to be consistent with rainfall in Sikkim in the east (Tambe et al 2012) and Uttarakhand in the central-western Himalaya (Agarwal et al 2012), it shows an inverse pattern with monthly rainfall in the western Himalayan springs of Kashmir (Negi et al 2012). These trends suggest that, in addition to precipitation, other causal factors and localized impacts should also be investigated.…”
Section: Springsmentioning
confidence: 90%
“…The study indicated the existence of a deep groundwater contribution to Himalayan springs. Agarwal et al (2012) monitored 50 springs, nine rain gauges and two river gauging stations in Uttarakhand, India, for 11 years, and estimated lag times of 1 to 30 days between precipitation and spring discharge. The flow lag times were used to demarcate areas for water retention structures to increase water availability.…”
Section: Integrating Historic Data Of Multiple Parametersmentioning
confidence: 99%
“…Springs are the major, if not the only, source of agricultural and domestic water for many rural communities in mountainous regions, such as the Himalayas (Bartarya 1991; Bartarya and Valdiya 1989;Negi and Joshi 2004;Pandit et al 2007;Vashisht and Sharma 2007;NDF 2014). Natural stressors (especially climate change) and improper watershed management have led to a decrease in discharge in many Himalayan springs (Agarwal et al 2012). For example, Valdiya and Bartarya (1989) reported a 40% reduction in spring discharge over a 35-year period (1951 to 1986) in the Kumaun Himalaya region, which was mostly attributed to changes in land-use patterns and vegetation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on regional studies, it has already been pointed out that the climate impacts are already occurring in the Greater Himalayas (Beniston 2003;Cruz et al 2007). The climatic variability in the region has also changed the rainfall pattern and the predictions show that there will be slight increase in rainfall along with greater intensity (Rees and Collins 2006;Singh et al 2008;Tambe et al 2011;Agarwal et al 2012). This changed pattern is further responsible for the reduced recharging of the spring catchments, whose impact is visible through the diminishing and/or drying-up of the springs during the recession period of the year.…”
Section: Introductionmentioning
confidence: 99%